BS EN 60404-6 Amd.1 Ed.3.0 AMD1. Magnetic materials. Part 6 Methods of measurement of the magnetic properties of magnetically soft metallic and powder materials at frequencies in the range 20 Hz to 100 kHz by the use of ring specimens (12th May 2020) - British Standards Institution,
No abstract available